Respuesta :

Answer:

[tex]\boxed{\sf \ \ \ x=\dfrac{3}{4} \ \ \ }[/tex]

Step-by-step explanation:

hello,

f(x)=x-1

[tex]g(x)=2x^2+3[/tex]

so

[tex]fog(x)=f(g(x))=f(2x^2+3)=2x^2+3-1=2x^2+2 \ and \\gof(x)=g(f(x))=g(x-1)=2(x-1)^2+3=2x^2-4x+2+3=2x^2-4x+5 \ \ So\\\fog(x)=gof(x) <=>2x^2+2=2x^2-4x+5\\<=>4x=5-2=3\\<=>x=\dfrac{3}{4}[/tex]

hope this helps

[tex]\frac{3}{4}[/tex]

The composition of a function is a process in which two functions [tex]f,g[/tex], are combined to produce a new function, [tex]h[/tex], with the formula [tex]h(x)=g(f(x))[/tex]. It means that the [tex]g[/tex] function is being applied to the [tex]x[/tex] function.

[tex]f(x)=x-1\\g(x)=2x^2+3[/tex]

[tex]f(g(x))=f(2x^2+3)[/tex]

            [tex]=2x^2+3-1\\=2x^2+2[/tex]

[tex]g(f(x))=g(x-1)[/tex]

           [tex]=2(x-1)^2+3\\=2x^2+2-4x+3\\=2x^2-4x+5[/tex]

[tex]f(g(x))=g(f(x))[/tex]

[tex]2x^2+2=2x^2-4x+5[/tex]

       [tex]4x=3[/tex]

        [tex]x=\frac{3}{4}[/tex]

For more information:

https://brainly.com/question/12431044?referrer=searchResults

ACCESS MORE